Let's solve for p.
[tex]y=4x3+4px2+16x−9[/tex]
Step 1: Flip the equation.
[tex]4px2+4x3+16x−9=y[/tex]
Step 2: Add -4x^3 to both sides.
[tex]4px2+4x3+16x−9+−4x3=y+−4x3[/tex]
[tex]4px2+16x−9=−4x3+y[/tex]
Step 3: Add -16x to both sides.
[tex]4px2+16x−9+−16x=−4x3+y+−16x[/tex]
[tex]4px2−9=−4x3−16x+y[/tex]
Step 4: Add 9 to both sides.
[tex]4px2−9+9=−4x3−16x+y+9[/tex]
[tex]4px2=−4x3−16x+y+9[/tex]
Step 5: Divide both sides by 4x^2.
4px² / 4x² = −4x³ − 16x + y + 9 / 4x²
Answer:
p = −4x³ − 16x + y + 9 / 4x²